PENERAPAN ISAK 35 PADA MASJID BAITUL HIDAYAH PUGER JEMBER - Ismi Darojatul Ula; Moh Halim; Ari Sita Nastiti (FKIP, Universitas Banten Jaya, 2021)
The purpose of this study was to determine the suitability of financial statements according to ISAK No. 35 and how the accounting record in the financial statements of Baitul Hidayah Puger Mosque with generally accepted accounting principles. The research was conducted at the Baitul Hidayah Puger Mosque using data collection techniques with interviews and documentation. The data analysis technique in this research was a qualitative descriptive analysis where the data was compiled and described based on the result of data collection on financial statements, then was compared with relevant theories to the problem, which could then be drawn a conclusion. Based on the result of the study, it could be concluded that the basis of recording applied at the Baitul Hidayah Puger Mosque was incomplete and not sequential according to applicable standards. The financial statements that made a report, a report on changes in net assets, a cash flow statements and notes on financial statements. Implementation of ISAK No. 35 Baitul Hidayah Puger Mosque was not in accordance with generally accepted accounting principles. The financial reporting of the Baitul Hidayah Mosque in Puger was not in accepted accounting principles.